Two new species and a new record of the genus Meganola Dyar, 1898 (Lepidoptera, Nolidae, Nolinae) from Laos - Cha, Yeong-Bin; László, Gyula M.; Bayarsaikhan, Ulziijargal; Ko, Jae-Ho; Lee, Tak-Gi; Jang, Chang-Moon; Kim, Hanul; Kim, Jeong-Nam; Bae, Yang-Seop (Zootaxa, 2021)
The paper contains the description of two new Meganola Dyar, 1898 species (M. canaliculata Cha & Bae, sp. n. and M. phuana Cha & Bae, sp. n.) and a new record of M. tetrodon (de Joannis, 1928) from Laos. Color figures of adults and genitalia of the examined species are provided.